EFFICACY OF DIFFERENT LEVELS OF VERMILIQUER ON YIELD ATTRIBUTES OF POTTED MARIGOLD IN BHARATPUR, CHITWAN. - B., Shrestha, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2015)
A pot culture experiment was conducted in Complete Randomized Design with four replications to assess the efficacy of different doses of vermiliquer on yield attributes of African marigold. Marigold planted in earthern pots were drenched with five different levels of vermiliquer i.e. Control, 25%, 50%, 75% and 100% vermiliquer at the rate of 150 ml/pot/week for five weeks. Study revealed that vermiliquer enhanced the yield characteristic of marigold. The maximum fresh weight of flower as well as dry weight was observed at 50 percent vermiliquer application followed by 75 percent vermiliquer application which was at par with 25 percent vermiliquer. Similarly the highest number of flower bud on marigold plant was found at 50 percent vermiliquer application (16) which was followed by 75 percent and 25 % vermiliquer application (14, 12) respectively which gave highest yield of flower per plant at the treatment of 50% vermiliquer application.